A Single Substitution of Valine to Glutamic Acid in the Omega-Like Loop Introduces a Penicillinase-Like Activity in MSMEG_6194 by Compromising its Role as DD-Carboxypeptidase - Aditya Prasad Panda; Debasmita Chatterjee; Anik Roy; Sarmistha Biswal; Anindya S. Ghosh (Current Microbiology, 2026)

Microplastic contamination across different feeding guilds of commercially important fishes from the Southeast Coast of India - Tejaswini Singh; Neha Kangujam; Suchitra Chanu Sanabam; Saoo Wan Emi Phyllei; S. M. Sundarapandian; K. Sivakumar; Subhankar Chatterjee (Environmental Monitoring and Assessment, 2026)

Impact of thermal and irradiation processing on phytochemical retention and fungal resistance in cluster beans (Cyamopsis tetragonoloba) - Aarti S. Kakatkar; Lipika Pansare Godambe; Ashika Debbarma; Prashant Kumar Mishra; Suchandra Chatterjee; Ravindranath Shashidhar (Food Chemistry, 2026)

A modelling approach to ascertain the memory induced by Findlater Jet in the Arabian Sea - Vikas Kumar Kushwaha; S Prasanna Kumar; F Feba; Lakshmi R. Shenoy; Abhisek Chatterjee; Ashok Karumuri (Climate Dynamics, 2026)
The formation of Findlater Jet (FJ) in the lower atmosphere over the Arabian Sea (AS) is an integral part of the Indian summer monsoon (ISM, June–September). Based on observations, our earlier study indicated that the FJ-induced heat signal during the ISM is potentially preserved in the upper ocean in the form of heat content in the southern AS until the following winter season. Through various sensitivity experiments with an ocean model, we could demonstrate the above and identify the processes that lead to the observed memory. We further demonstrate that the simulated mixed layer depth and the upper ocean heat content are higher in the southern AS during a flood monsoon year compared to a drought year. This is attributed to a relatively stronger FJ-induced wind stress curl during the flood summer monsoon, which deepens the thermocline and results in higher heat retention in the southern AS during the subsequent winter and spring seasons. The accumulated heat enhances pre-monsoon rainfall over the west Indian coastal region and, in turn, influences the ensuing monsoon rainfall.

Machine Learning-based Prediction and Optimization of Photocatalytic Degradation of Methylene Blue Using TiO₂, Fe₂O₃, and Ti–Fe Composite Nanomaterials - Sweety Khut; Aajinkya Singh; Arpan Chatterjee; Ankush B. Bindwal; Pravin D. Patil; Shamraja S. Nadar; Manishkumar S. Tiwari (Environmental Processes, 2026)

Seismic Site Classification, Stratigraphy Assessment and SPT-Vs Correlation for Madhubani and Adjoining Regions of Bihar Based on In-Situ Geotechnical and MASW Investigations - Abhileen Chatterjee; Hrik Chaudhury; R. V. S. Jenny Laura; Aman Alok; Abhishek Kumar (Geotechnical and Geological Engineering, 2026)

The impact of coal ash fusion on blast furnace Decarbonization: A study without and with natural gas co-injection - Rajeswar Chatterjee; S Krishna; S Varunkumar; Samik Nag (Fuel, 2026)

Advanced workflows for UAV-based crop height estimation using structure from motion (SfM) point clouds - Sumantra Chatterjee; Bala Ram Sapkota; Gurjinder S. Baath; K. Colton Flynn; Douglas R. Smith (Remote Sensing Applications: Society and Environment, 2026)

Beyond the target: the ecotoxicological impact of flubendiamide in natural ecosystems - T. Roy; S. Ghosh; A. H. Mandal; N. C. Saha; S. Chatterjee; D. S. Paria; C. R. Multisanti; C. Faggio; S. Saha (International Journal of Environmental Science and Technology, 2026)

Rapid 21st Century Warming in the Southern Subtropical Indian Ocean Driven by Altered Inter‐Basin Connections - C. K. Sajidh; Abhisek Chatterjee; Raghu Murtugudde; Michael J. McPhaden; S. S. C. Shenoi; P. N. Vinayachandran (International Journal of Climatology, 2026)
The Indian Ocean has been warming rapidly over the last few decades. However, this warming has not been uniform, with the southern subtropical Indian Ocean (STIO, 15°S–35°S) cooling until the late 20th century and then warming abruptly. We show that the Indonesian Throughflow (ITF) into the Indian Ocean exhibits strong decadal variability with a weaker negative trend over the recent decades, and hence cannot explain the continued heat gain by the upper ocean of the STIO at a rate of 0.41 (± 0.02) × 10 22 J/decade. An increased ITF during the hiatus in global surface warming initiated the STIO warming, resulting in a weaker Mascarene high and its decoupling from the Southern Ocean atmospheric variability. This enhanced Tasman inflow into the Indian Ocean and weakened Agulhas outflow offsetting the recently weakened ITF, caused a positive feedback that continued to warm the upper ocean of the STIO.

Anticancer potential of phytocompound isolated from Asystasia gangetica leaves: extraction optimization, characterization, and toxicity assessment - Jayalakshmi Ramasamy; Latha Subbiah; Akshath U. S.; Niladri Sekhar Chatterjee; Swarnalatha Kodidela; Chandra Mohan Mittameedi; Raja Ganesan; Pavan Kumar Dara; Celine Hilda Mary S.; Selvamani Palanisamy (Natural Product Research, 2025)

Enhanced carbon capture and medium chain fatty acid production using microbial electrosynthesis: Role of electrode surface area - Narnepati Krishna Chaitanya; Akanksha Rajpurohit; Pavithra S. Nair; Pritha Chatterjee (Bioresource Technology, 2025)

Uncovering microbial drivers and regulatory edaphic factors for DNRA-nitrogen recovery under diverse rice agro-ecosystems - Megha Kaviraj; Upendra Kumar; S. N. Chatterjee; M. Shahid; A. K. Nayak (Plant and Soil, 2025)

Vehicle-specific power-based emission modeling using unsupervised machine learning techniques - Chandrashekar Chowdappa; Pritha Chatterjee; Digvijay S. Pawar (Environmental Science and Pollution Research, 2025)

Lab-on-a chip electrochemical sensing platform for simultaneous, ultra-sensitive and on-spot detection of 4-aminosalicylic acid and 5-aminosalicylic acid based on synergistic potential of chitosan functionalized MWCNTs supported on Ni doped Bi2S3 - Darshana Chatterjee; S. Ravi P. Silva; Ida Tiwari (Chemosphere, 2025)

Monitoring endocrine-disrupting compounds and risk assessment in the southwest coastal regions of India using black clams (Villorita cyprinoides) as an indicator - Nasreen Nazar; S. Sreejith; J. Bindu; Nikita Gopal; Niladri Sekhar Chatterjee (Marine Pollution Bulletin, 2025)

Untargeted metabolomics offers insights into the risks of chronic exposure to mixtures of polycyclic aromatic hydrocarbons at environmentally relevant low concentrations - Nasreen Nazar; A. S. Athira; Ranjit Kumar Nadella; Satyen Kumar Panda; Kaushik Banerjee; Niladri Sekhar Chatterjee (Environmental Geochemistry and Health, 2025)

Enhancing LAI estimation using multispectral imagery and machine learning: A comparison between reflectance-based and vegetation indices-based approaches - Sumantra Chatterjee; Gurjinder S. Baath; Bala Ram Sapkota; K.Colton Flynn; Douglas R. Smith (Computers and Electronics in Agriculture, 2025)

Modified emission and scaling factors for methane and nitrous oxide in rice system of India: A country specific disaggregate approach - Pratap Bhattacharyya; A. Bhatia; N. Jain; D. Chatterjee; S. Mohanty; M. Prabhakar; Pratibha M; N.N. Jambhulkar; S. Ananthakrishnan; S.K. Nayak; A.K. Nayak; H. Pathak (Journal of Environmental Management, 2025)

Shelf-life extension of ready-to-cook Tilapia (Oreochromis spp.) fish balls using hurdle technology - Raj Kamal Gautam; Aarti S. Kakatkar; Ashika Debbarma; Prashant K. Mishra; Vivekanand Kumar; R Shashidhar; Suchandra Chatterjee (Food Bioscience, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Impact of cell voltage on synthesis of caproic acid from carbon dioxide and ethanol in direct current powered microbial electrosynthesis cell - Narnepati Krishna Chaitanya; Pavithra S. Nair; Akanksha Rajpurohit; Pritha Chatterjee (Bioresource Technology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Expanding Policies to Support Culturally Tailored Nutrition Care for Diverse Older Adults and Their Family Caregivers - L. Gutierrez Munoz; S. Shrivastava; S. Arevalo; M. Karkare; S. Chatterjee; Y. Caraballo Lopez; S. Ranjan; A. Hinojosa; M. Vishwanathan; S. Jacobo; M. Barragan; M. Raj (Journal of the Academy of Nutrition and Dietetics, 2024)

A two-tier approach for the detection of contaminants and adulterants in sunflower oil to protect consumer safety - Tareq H. Talib; Niladri S. Chatterjee; Kaushik Banerjee; Awanwee Petchkongkaew; Christopher T. Elliott; Di Wu (Trends in Food Science & Technology, 2024)

Data processing of visible emission line coronagraph onboard ADITYA-L1 - Muthu Priyal; Jagdev Singh; B. Raghavendra Prasad; Chavali Sumana; Varun Kumar; Shalabh Mishra; S.N. Venkata; G. Sindhuja; K. Sasikumar Raja; Amit Kumar; Sanal krishnan; Bhavana S. Hegde; et al. (Advances in Space Research, 2024)

Assessment of groundwater level using satellite-based hydrological parameters in North-West India: A deep learning approach - Pranshu Pranjal; Dheeraj Kumar; Ashish Soni; R. S. Chatterjee (Earth Science Informatics, 2024)

Potential of nano-phytoremediation of heavy metal contaminated soil: emphasizing the role of mycorrhizal fungi in the amelioration process - A. Mitra; S. Kataki; S. Chatterjee; D. K. Gupta (International Journal of Environmental Science and Technology, 2024)

Modeling real-world diesel car tailpipe emissions using regression-based approaches - C Chandrashekar; Pritha Chatterjee; Digvijay S. Pawar (Transportation Research Part D: Transport and Environment, 2024)

A review on environmental impacts of renewable energy for sustainable development - D. Gayen; R. Chatterjee; S. Roy (International Journal of Environmental Science and Technology, 2024)

Noise vulnerability assessment using an integrated approach of multi-criteria decision-making model and geospatial techniques - S. Pahari; N. Das Chatterjee; N. K. Barman (International Journal of Environmental Science and Technology, 2024)

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

Drug Dissolution in Oral Drug Absorption: Workshop Report - Kimberly Raines; Payal Agarwal; Patrick Augustijns; Alaadin Alayoubi; Lucas Attia; Annette Bauer-Brandl; Martin Brandl; Parnali Chatterjee; Hansong Chen; Yuly Chiang Yu; Carrie Coutant; Ana Luisa Coutinho; et al. (The AAPS Journal, 2023)
The in-person workshop “Drug Dissolution in Oral Drug Absorption” was held on May 23–24, 2023, in Baltimore, MD, USA. The workshop was organized into lectures and breakout sessions. Three common topics that were re-visited by various lecturers were amorphous solid dispersions (ASDs), dissolution/permeation interplay, and in vitro methods to predict in vivo biopharmaceutics performance and risk. Topics that repeatedly surfaced across breakout sessions were the following: (1) meaning and assessment of “dissolved drug,” particularly of poorly water soluble drug in colloidal environments ( e.g. , fed conditions, ASDs); (2) potential limitations of a test that employs sink conditions for a poorly water soluble drug; (3) non-compendial methods ( e.g. , two-stage or multi-stage method, dissolution/permeation methods); (4) non-compendial conditions ( e.g. , apex vessels, non-sink conditions); and (5) potential benefit of having both a quality control method for batch release and a biopredictive/biorelevant method for biowaiver or bridging scenarios. An identified obstacle to non-compendial methods is the uncertainty of global regulatory acceptance of such methods.

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Unravelling the dynamics and causes of land subsidence in the National Capital Territory of Delhi, India, by spaceborne and in situ observations - R. S. Chatterjee; Pranshu Pranjal; Suresh Kannaujiya; Shailaja Thapa; Ashutosh Bhardwaj; Uma Kapoor; S. N. Dwivedi; Rajesh Chandra; Rajiv Kumar Srivastava; S. K. Singh; Harsh Kumar; Rajarshi Bhattacharjee; et al. (Bulletin of Engineering Geology and the Environment, 2023)

Unraveling the potential of microbes in decomposition of organic matter and release of carbon in the ecosystem - Taqi Raza; Muhammad Farhan Qadir; Khuram Shehzad Khan; Neal S. Eash; Muhammad Yousuf; Sumanta Chatterjee; Rabia Manzoor; Sana ur Rehman; Joel Nathaniel Oetting (Journal of Environmental Management, 2023)

An evolving perspective on the fluoride mitigation techniques - S. K. Das; A. K. Pramanik; R. K. Das; A. Chatterjee (International Journal of Environmental Science and Technology, 2023)

Reassessing the availability of crop residue as a bioenergy resource in India: A field-survey based study - Taveen S. Kapoor; Chimurkar Navinya; Gupta Anurag; Pradnya Lokhande; Shubham Rathi; Anubha Goel; Renuka Sharma; Rahul Arya; Tuhin K. Mandal; K.P. Jithin; Shiva Nagendra; Mohd Imran; et al. (Journal of Environmental Management, 2023)

Parametric maps of spatial two-tissue compartment model for prostate dynamic contrast enhanced MRI - comparison with the standard tofts model in the diagnosis of prostate cancer - Xueyan Zhou; Xiaobing Fan; Aritrick Chatterjee; Ambereen Yousuf; Tatjana Antic; Aytekin Oto; Gregory S. Karczmar (Physical and Engineering Sciences in Medicine, 2023)

In-silico and in-vitro hybrid approach to identify glucagon-like peptide-1 receptor agonists from anti-diabetic natural products - Debanjan Chatterjee; Nazmina Vhora; Ashutosh Goswami; Aishwarya Hiray; Alok Jain; Abhijeet S. Kate (Natural Product Research, 2023)

Evaluation of Paecilomyces tenuis producing Huperzine A for the management of root-knot nematode Meloidogyne incognita (Nematoda: Meloidogynidae) - Rami Kassam; Nisha Jaiswal; Alkesh Hada; Victor Phani; Jyoti Yadav; Roli Budhwar; Jeffrey Godwin; Madhurima Chatterjee; Chaitra G. Bhat; Jigni Mishra; Virendra S. Rana; Aditi Kundu; et al. (Journal of Pest Science, 2023)

Synthetic chalcone 1-(4-Fluoro-phenyl)-3-phenyl-propenone with high nematicidal potential against the root-knot nematode Meloidogyne incognita - Prakash Banakar; Alkesh Hada; Victor Phani; Madhurima Chatterjee; Divya Singh; Jyoti Yadav; Virendra S. Rana; Najam A. Shakil; Uma Rao (Indian Phytopathology, 2023)

Hydrated komatiites as a source of water for TTG formation in the Archean - R. Tamblyn; J. Hermann; D. Hasterok; P. Sossi; T. Pettke; S. Chatterjee (Earth and Planetary Science Letters, 2023)

Sustainable enzymatic treatment of organic waste in a framework of circular economy - Debkumar Chakraborty; Sulogna Chatterjee; Avanthi Althuri; Sankar Ganesh Palani; S. Venkata Mohan (Bioresource Technology, 2023)

Effect of ajwain (Trachyspermum ammi) extract and gamma irradiation on the shelf-life extension of rohu (Labeo rohita) and seer (Scomberomorus guttatus) fish steaks during chilled storage - Prashant K. Mishra; Aarti S. Kakatkar; Raj Kamal Gautam; Vivekanand Kumar; Ashika Debbarma; Suchandra Chatterjee (Food Research International, 2023)

Magmatic inflation, miniature dyke intrusion and prolonged torrential rainfall led to the emergence of the 2018 aseismic fissure in Kenya - R. S. Chatterjee; Kishan Kumar; Pranshu Pranjal; Suresh Kannaujiya; Prakash Chauhan (Natural Hazards, 2023)

Phlorotannins–bioactivity and extraction perspectives - Lekshmi R. G. Kumar; Preethy Treesa Paul; K. K. Anas; C. S. Tejpal; N. S. Chatterjee; T. K. Anupama; Suseela Mathew; C. N. Ravishankar (Journal of Applied Phycology, 2022)

Relic surface water (clay-pore water) input triggers arsenic release into the shallow groundwater of Bengal aquifers - Pousali Pathak; Prosenjit Ghosh; Sanchita Banerjee; R S Chatterjee; Noor Muzakkira; Pradip K Sikdar; Utsab Ghosal; Mao-Chang Liang; Kathiravan Meeran (Journal of Earth System Science, 2022)

Long-Term Yield of Rice–Rice System with Different Nutrient Management in Eastern India: Effect of Air Temperature Variability in Dry Season - Manish Debnath; Rahul Tripathi; Sumanta Chatterjee; Md. Shahid; B. Lal; Priyanka Gautam; N. N. Jambhulkar; S. Mohanty; D. Chatterjee; B. B. Panda; P. K. Nayak; P. Bhattacharyya; et al. (Agricultural Research, 2022)

Multifunctional lipidic nanocarriers for effective therapy of glioblastoma: recent advances in stimuli-responsive, receptor and subcellular targeted approaches - Manasa Manjunath Hegde; Suma Prabhu; Srinivas Mutalik; Abhishek Chatterjee; Jayant S. Goda; B. S. Satish Rao (Journal of Pharmaceutical Investigation, 2022)
Background Glioblastoma, or glioblastoma multiforme (GBM), remains a fatal cancer type despite the remarkable progress in understanding the genesis and propagation of the tumor. Current treatment modalities, comprising mainly of surgery followed by adjuvant chemoradiation, are insufficient for improving patients' survival owing to existing hurdles, including the blood–brain barrier (BBB). In contemporary practice, the prospect of long-term survival or cure continues to be a challenge for patients suffering from GBM. This review provides an insight into the drug delivery strategies and the significant efforts made in lipid-based nanoplatform research to circumvent the challenges in optimal drug delivery in GBM. Area covered Owing to the unique properties of lipid-based nanoplatforms and advancements in clinical translation, this article describes the application of various stimuli-responsive lipid nanocarriers and tumor subcellular organelle-targeted therapy to give an idea about the strategies that can be applied to enhance site-specific drug delivery for GBM. Furthermore, active targeting of drugs via surface-modified lipid-based nanostructures and recent findings in alternative therapeutic platforms such as gene therapy, immunotherapy, and multimodal therapy have also been overviewed. Expert opinion Lipid-based nanoparticles stand out among the other nanocarriers explored for GBM drug delivery, as they support both passive and active drug targeting by crossing/bypassing the BBB at the same time minimizing toxicity and projects better pharmacological parameters. Although these nanocarriers could be a plausible choice for treating GBM, in-depth research is essential to advance neuro-oncology research and enhance outcomes in patients with brain tumors.

Modelling the Spatial Variation of Methane and Nitrous Oxide Emission from Rice Fields Using DNDC Model - Rahul Tripathi; M. Majhi; S. G. Sahu; S. Mohanty; K. C. Moharana; Md Shahid; C. K. Swain; B. Lal; P. Gautam; P. K. Dash; D. Chatterjee; A. Kumar; et al. (Journal of the Indian Society of Remote Sensing, 2021)

Variation of salinity in the Sundarbans Estuarine System during the Equinoctial Spring tidal phase of March 2011 - Meenakshi Chatterjee; D Shankar; V Vijith; G K Sen; D Sundar; G S Michael; P Amol; Abhisek Chatterjee; P Sanyal; Siddhartha Chatterjee; Anwesha Basu; Saranya Chakraborti; et al. (Journal of Earth System Science, 2021)

Performance improvement of 500 MW coal power plant at low temperature steam condition by suitable operation practice - S. J. Chatterjee; G. Khankari; S. Karmakar (International Journal of Energy and Water Resources, 2021)

Impact of lockdown associated with COVID19 on air quality and emissions from transportation sector: case study in selected Indian metropolitan cities - Tejaswini Eregowda; Pritha Chatterjee; Digvijay S. Pawar (Environment Systems and Decisions, 2021)

Seasonal Transport Pathway and Sources of Carbonaceous Aerosols at an Urban Site of Eastern Himalaya - Akansha Rai; Sauryadeep Mukherjee; Nikki Choudhary; Abhinandan Ghosh; A. Chatterjee; T. K. Mandal; S. K. Sharma; R. K. Kotnala (Aerosol Science and Engineering, 2021)

Are ocean-moored buoys redundant for prediction of Indian monsoon? - Maheswar Pradhan; Ankur Srivastava; Suryachandra A. Rao; Deep Sankar Banerjee; Abhisek Chatterjee; P. A. Francis; O. P. Sreejith; M. Das Gupta; V. S. Prasad (Meteorology and Atmospheric Physics, 2021)

Agricultural GHG emission and calorie intake nexus among different socioeconomic households of rural eastern India - Rahul Tripathi; B. Dhal; Md Shahid; S. K. Barik; A. D. Nayak; B. Mondal; S. D. Mohapatra; D. Chatterjee; B. Lal; Priyanka Gautam; N. N. Jambhulkar; Nuala Fitton; et al. (Environment, Development and Sustainability, 2021)

Genome‐wide variation in DNA methylation linked to developmental stage and chromosomal suppression of recombination in white‐throated sparrows - Dan Sun; Thomas S. Layman; Hyeonsoo Jeong; Paramita Chatterjee; Kathleen Grogan; Jennifer R. Merritt; Donna L. Maney; Soojin V. Yi (Molecular Ecology, 2021)
Much of our knowledge on regulatory impacts of DNA methylation has come from laboratory‐bred model organisms, which may not exhibit the full extent of variation found in wild populations. Here, we investigated naturally‐occurring variation in DNA methylation in a wild avian species, the white‐throated sparrow ( Zonotrichia albicollis ). This species offers exceptional opportunities for studying the link between genetic differentiation and phenotypic traits because of a nonrecombining chromosome pair linked to both plumage and behavioural phenotypes. Using novel single‐nucleotide resolution methylation maps and gene expression data, we show that DNA methylation and the expression of DNA methyltransferases are significantly higher in adults than in nestlings. Genes for which DNA methylation varied between nestlings and adults were implicated in development and cell differentiation and were located throughout the genome. In contrast, differential methylation between plumage morphs was concentrated in the nonrecombining chromosome pair. Interestingly, a large number of CpGs on the nonrecombining chromosome, localized to transposable elements, have undergone dramatic loss of DNA methylation since the split of the ZAL2 and ZAL2 m chromosomes. Changes in methylation predicted changes in gene expression for both chromosomes. In summary, we demonstrate changes in genome‐wide DNA methylation that are associated with development and with specific functional categories of genes in white‐throated sparrows. Moreover, we observe substantial DNA methylation reprogramming associated with the suppression of recombination, with implications for genome integrity and gene expression divergence. These results offer an unprecedented view of ongoing epigenetic reprogramming in a wild population.

Hybrid larval lethality of Drosophila is caused by parent-of-origin expression: an insight from imaginal discs morphogenesis of Lhr pausing rescue hybrids of D. melanogaster and D. simulans - R. N. Chatterjee; S. Kuthe; Piyali Chatterje (The Nucleus, 2021)

Assessment of groundwater depletion–induced land subsidence and characterisation of damaging cracks on houses: a case study in Mohali-Chandigarh area, India - Neha Kadiyan; R. S. Chatterjee; Pranshu Pranjal; Pankaj Agrawal; S. K. Jain; M. L. Angurala; A. K. Biyani; M. S. Sati; Dheeraj Kumar; Ashutosh Bhardwaj; P. K. Champati Ray (Bulletin of Engineering Geology and the Environment, 2021)

Backyard poultry farming for sustained production and enhanced nutritional and livelihood security with special reference to India: a review - U. Rajkumar; S. V. Rama Rao; M. V. L. N. Raju; R. N. Chatterjee (Tropical Animal Health and Production, 2021)

Study on aerobic degradation of 2,4,6-trinitrotoluene (TNT) using Pseudarthrobacter chlorophenolicus collected from the contaminated site - Jyoti Lamba; Shalini Anand; Jayanti Dutta; Soumya Chatterjee; Shilpi Nagar; S. Mary Celin; Pramod Kumar Rai (Environmental Monitoring and Assessment, 2021)

Use of IRS-1C and Its Follow-On Missions for Geological Applications: A Review - S. K. Srivastav; R. S. Chatterjee; Deepali Kapoor; G. Sreenivasan; E. V. R. Parthasaradhy (Journal of the Indian Society of Remote Sensing, 2021)

Rajgad GPB: A megaporphyritic flow field, Western Deccan Volcanic Province, India - Priyanka Shandilya; Poushali Chatterjee; Kondepudi Pattabhiram; Makarand Bodas; Kanchan Pande; Vivek S Kale (Journal of Earth System Science, 2020)

Genetic analysis of growth and egg production traits in synthetic colored broiler female line using animal model - L. Leslie Leo Prince; K. S. Rajaravindra; U. Rajkumar; B. L. N. Reddy; C. Paswan; S. Haunshi; R. N. Chatterjee (Tropical Animal Health and Production, 2020)

Effect of reducing energy intake during the dry period on milk production, udder health, and body condition score of Jersey crossbred cows in the tropical lower Gangetic region - Amit Kumar Singh; Champak Bhakat; D. K. Mandal; A. Mandal; S. Rai; A. Chatterjee; M. K. Ghosh (Tropical Animal Health and Production, 2020)

Rain water resource management in mango orchards through micro-catchments - A. Mishra; A. Waghaye; C. Chatterjee; S. K. Rautaray (Sustainable Water Resources Management, 2020)

Effects of integrated farming system and rainwater harvesting on livelihood improvement in North-Eastern region of India compared to traditional shifting cultivation: evidence from an action research - Sanjay Kumar Ray; Dibyendu Chatterjee; D. J. Rajkhowa; S. K. Baishya; S. Hazarika; S. Paul (Agroforestry Systems, 2020)

Seasonal Variation of OC, EC, and WSOC of PM10 and Their CWT Analysis Over the Eastern Himalaya - Akansha Rai; Sauryadeep Mukherjee; Abhijit Chatterjee; Nikki Choudhary; Garima Kotnala; T. K. Mandal; S. K. Sharma (Aerosol Science and Engineering, 2020)

Water vapor flux in tropical lowland rice - Dibyendu Chatterjee; Amaresh Kumar Nayak; S. Vijayakumar; Manish Debnath; Sumanta Chatterjee; Chinmaya Kumar Swain; Priyanka Bihari; S. Mohanty; Rahul Tripathi; Mohammad Shahid; Anjani Kumar; H. Pathak (Environmental Monitoring and Assessment, 2019)

Bioreduction of toxic hexavalent chromium by novel indigenous microbe Brevibacillus agri isolated from tannery wastewater - S. Chatterjee; K. Shekhawat; N. Gupta (International Journal of Environmental Science and Technology, 2019)

Wyrtki Jets: Role of intraseasonal forcing - S Prerna; Abhisek Chatterjee; A Mukherjee; M Ravichandran; S S C Shenoi (Journal of Earth System Science, 2019)

Assessment of Land Surface Subsidence Due to Underground Metal Mining Using Integrated Spaceborne Repeat-Pass Differential Interferometric Synthetic Aperture Radar (DInSAR) Technique and Ground Based Observations - Md Soyeb Alam; Dheeraj Kumar; R. S. Chatterjee; Vijay Upreti (Journal of the Indian Society of Remote Sensing, 2018)

A Chemosensitizer Drug: Disulfiram Prevents Doxorubicin-Induced Cardiac Dysfunction and Oxidative Stress in Rats - Varsha K. Sonawane; Umesh B. Mahajan; Sachin D. Shinde; Subhajit Chatterjee; Sandip S. Chaudhari; Harshada A. Bhangale; Shreesh Ojha; Sameer N. Goyal; Chanakya N. Kundu; Chandragouda R. Patil (Cardiovascular Toxicology, 2018)

ER stress and genomic instability induced by gamma radiation in mice primary cultured glial cells - Jit Chatterjee; Rajesha K. Nairy; Jaldeep Langhnoja; Ashutosh Tripathi; Rajashekhar K. Patil; Prakash P. Pillai; Mohammed S. Mustak (Metabolic Brain Disease, 2018)

Leveraging model-informed approaches for drug discovery and development in the cardiovascular space - Marissa F. Dockendorf; Ryan C. Vargo; Ferdous Gheyas; Anne S. Y. Chain; Manash S. Chatterjee; Larissa A. Wenning (Journal of Pharmacokinetics and Pharmacodynamics, 2018)

Measuring potassium fractions is not sufficient to assess the long-term impact of fertilization and manuring on soil’s potassium supplying capacity - Debarup Das; Amaresh Kumar Nayak; V. K. Thilagam; Dibyendu Chatterjee; M. Shahid; Rahul Tripathi; S. Mohanty; Anjani Kumar; B. Lal; Priyanka Gautam; B. B. Panda; S. S. Biswas (Journal of Soils and Sediments, 2018)

Clinical application of modified bag-of-features coupled with hybrid neural-based classifier in dengue fever classification using gene expression data - Sankhadeep Chatterjee; Nilanjan Dey; Fuqian Shi; Amira S. Ashour; Simon James Fong; Soumya Sen (Medical & Biological Engineering & Computing, 2018)

Mortality associated with candidemia in non-neutropenic cancer patients is not less compared to a neutropenic cohort of cancer patients - G. Goel; M. Chandy; A. Bhattacharyya; S. Banerjee; S. Chatterjee; S. Mullick; S. Sinha; K. Sengupta; K. Dhar; S. Bhattacharya; S. Rudramurthy; A. Chakrabarti (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

ENSO related SST anomalies and relation with surface heat fluxes over south Pacific and Atlantic - S. Chatterjee; M. Nuncio; K. Satheesan (Climate Dynamics, 2017)

A multi-isotope approach (O, H, C, S, B and Sr) to understand the source of water and solutes in some the thermal springs from West Coast geothermal area, India - Sitangshu Chatterjee; Md. Arzoo Ansari; Archana S. Deodhar; Uday Kumar Sinha; Ashutosh Dash (Arabian Journal of Geosciences, 2017)

Evidence for the existence of Persian Gulf Water and Red Sea Water in the Bay of Bengal - Vineet Jain; D. Shankar; P. N. Vinayachandran; A. Kankonkar; Abhisek Chatterjee; P. Amol; A. M. Almeida; G. S. Michael; A. Mukherjee; Meenakshi Chatterjee; R. Fernandes; R. Luis; et al. (Climate Dynamics, 2017)

Erratum to: Growth arrest of lung carcinoma cells (A549) by polyacrylate-anchored peroxovanadate by activating Rac1-NADPH oxidase signalling axis - Nirupama Chatterjee; Tarique Anwar; Nashreen S. Islam; T. Ramasarma; Gayatri Ramakrishna (Molecular and Cellular Biochemistry, 2017)

Projecting Future Crop Evapotranspiration and Irrigation Requirement of Potato in Lower Gangetic Plains of India using the CROPWAT 8.0 Model - Saon Banerjee; S. Chatterjee; S. Sarkar; S. Jena (Potato Research, 2016)

Growth arrest of lung carcinoma cells (A549) by polyacrylate-anchored peroxovanadate by activating Rac1-NADPH oxidase signalling axis - Nirupama Chatterjee; Tarique Anwar; Nashreen S. Islam; T. Ramasarma; Gayatri Ramakrishna (Molecular and Cellular Biochemistry, 2016)

Sequence Determination of an Antioxidant Peptide Obtained by Enzymatic Hydrolysis of Oyster Crassostrea madrasensis (Preston) - K. K. Asha; K. R. Remya Kumari; K. Ashok Kumar; Niladri S. Chatterjee; R. Anandan; Suseela Mathew (International Journal of Peptide Research and Therapeutics, 2016)

Spatio-temporal variation in chemical characteristics of PM10 over Indo Gangetic Plain of India - S. K. Sharma; T. K. Mandal; M. K. Srivastava; A. Chatterjee; Srishti Jain; M. Saxena; B. P. Singh; Saraswati; A. Sharma; A. Adak; S. K.Ghosh (Environmental Science and Pollution Research, 2016)

Assessing current genetic status of the Hainan gibbon using historical and demographic baselines: implications for conservation management of species of extreme rarity - J. V. Bryant; D. Gottelli; X. Zeng; X. Hong; B. P. L. Chan; J. R. Fellowes; Y. Zhang; J. Luo; C. Durrant; T. Geissmann; H. J. Chatterjee; S. T. Turvey (Molecular Ecology, 2016)
Evidence‐based conservation planning is crucial for informing management decisions for species of extreme rarity, but collection of robust data on genetic status or other parameters can be extremely challenging for such species. The Hainan gibbon, possibly the world's rarest mammal, consists of a single population of ~25 individuals restricted to one protected area on Hainan Island, China, and has persisted for over 30 years at exceptionally low population size. Analysis of genotypes at 11 microsatellite loci from faecal samples for 36% of the current global population and tissue samples from 62% of existing historical museum specimens demonstrates limited current genetic diversity ( Na = 2.27, Ar = 2.24, H e = 0.43); diversity has declined since the 19th century and even further within the last 30 years, representing declines of ~30% from historical levels ( Na = 3.36, Ar = 3.29, H e = 0.63). Significant differentiation is seen between current and historical samples ( F ST = 0.156, P = 0.0315), and the current population exhibits extremely small N e (current N e = 2.16). There is evidence for both a recent population bottleneck and an earlier bottleneck, with population size already reasonably low by the late 19th century (historical N e = 1162.96). Individuals in the current population are related at the level of half‐ to full‐siblings between social groups, and full‐siblings or parent–offspring within a social group, suggesting that inbreeding is likely to increase in the future. The species' current reduced genetic diversity must be considered during conservation planning, particularly for expectations of likely population recovery, indicating that intensive, carefully planned management is essential.

Citric Acid Induced Potassium and Silicon Release in Alfisols, Vertisols and Inceptisols of India - Dibyendu Chatterjee; S. C. Datta; K. M. Manjaiah (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Targeting polo-like kinase 1 suppresses essential functions of alloreactive T cells - Carsten Berges; Manik Chatterjee; Max S. Topp; Hermann Einsele (Immunologic Research, 2016)

Drosophila curviceps Species-Group (Diptera: Drosophilidae) from India, with Description of a New Species and Redescription of a Known Species - Sushmika Pradhan; Pradeep C. Sati; Rajendra S. Fartyal; Rabindra N. Chatterjee; Manisha Sarswat; Mukul C. Kandpal; Birendra K. Singh (Proceedings of the Zoological Society, 2015)

Variation of Stable Carbon and Nitrogen Isotopic Composition of PM10 at Urban Sites of Indo Gangetic Plain (IGP) of India - S. K. Sharma; T. K. Mandal; D. M. Shenoy; Pratirupa Bardhan; Manoj K. Srivastava; A. Chatterjee; Mohit Saxena; Saraswati; B. P. Singh; S. K. Ghosh (Bulletin of Environmental Contamination and Toxicology, 2015)

Detecting, mapping and monitoring of land subsidence in Jharia Coalfield, Jharkhand, India by spaceborne differential interferometric SAR, GPS and precision levelling techniques - R S Chatterjee; Shailaja Thapa; K B Singh; G Varunakumar; E V R Raju (Journal of Earth System Science, 2015)

Proceedings of the second international molecular pathological epidemiology (MPE) meeting - Shuji Ogino; Peter T. Campbell; Reiko Nishihara; Amanda I. Phipps; Andrew H. Beck; Mark E. Sherman; Andrew T. Chan; Melissa A. Troester; Adam J. Bass; Kathryn C. Fitzgerald; Rafael A. Irizarry; Karl T. Kelsey; et al. (Cancer Causes & Control, 2015)

Intersex (ix) mutations of Drosophila melanogaster cause nonrandom cell death in genital disc and can induce tumours in genitals in response to decapentaplegic (dpp disk ) mutations - R. N. CHATTERJEE; P. CHATTERJEE; S. KUTHE; M. ACHARYYA-ARI; R. CHATTERJEE (Journal of Genetics, 2015)

Geostatistical approach for management of soil nutrients with special emphasis on different forms of potassium considering their spatial variation in intensive cropping system of West Bengal, India - Sourov Chatterjee; Priyabrata Santra; Kaushik Majumdar; Debjani Ghosh; Indranil Das; S. K. Sanyal (Environmental Monitoring and Assessment, 2015)

Role and Present Status of Biotechnology in Augmenting Poultry Productivity in India - C. Paswan; T. K. Bhattacharya; C. S. Nagaraj; R. N. Chatterjee; P. Guru Vishnu (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

The high prevalence of serine protease autotransporters of Enterobacteriaceae (SPATEs) in Escherichia coli causing neonatal septicemia - R. Tapader; S. Chatterjee; A. K. Singh; P. Dayma; S. Haldar; A. Pal; S. Basu (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Efficient synthesis of 4-oxo-4,5-dihydrothieno[3,2- $$c$$ c ]quinoline-2-carboxylic acid derivatives from aniline - Arindam Chatterjee; Stephen J. Cutler; Ikhlas A. Khan; John S. Williamson (Molecular Diversity, 2014)

Joint effects between five identified risk variants, allergy, and autoimmune conditions on glioma risk - Mahboobeh Safaeian; Preetha Rajaraman; Patricia Hartge; Meredith Yeager; Martha Linet; Mary Ann Butler; Avima M. Ruder; Mark P. Purdue; Ann Hsing; Laura Beane-Freeman; Jane A. Hoppin; Demetrius Albanes; et al. (Cancer Causes & Control, 2013)

Tidal variations in the Sundarbans Estuarine System, India - MEENAKSHI CHATTERJEE; D SHANKAR; G K SEN; P SANYAL; D SUNDAR; G S MICHAEL; ABHISEK CHATTERJEE; P AMOL; DEBABRATA MUKHERJEE; K SUPRIT; A MUKHERJEE; V VIJITH; et al. (Journal of Earth System Science, 2013)

New Mediterranean Marine biodiversity records (June 2013) - I. SIOKOU; A.S. ATES; D. AYAS; J. BEN SOUISSI; T. CHATTERJEE; M. DIMIZA; H. DURGHAM; K. DOGRAMMATZI; D. ERGUDEN; V. GERAKARIS; M. GREGO; Y. ISSARIS; et al. (Mediterranean Marine Science, 2013)
This paper concerns records of species that have extended their distribution in the Mediterranean Sea. The finding of the rare brackish angiosperm Althenia filiformis in the island of Cyprus is interesting since its insertion in the Red Data Book of the Flora of Cyprus is suggested. The following species enriched the flora or fauna lists of the relevant countries: the red alga Sebdenia dichotoma (Greece), the hydrachnid mite Pontarachna adriatica (Slovenia), and the thalassinid Gebiacantha talismani (Turkey). Several alien species were recorded in new Mediterranean localities. The record of the burrowing goby Trypauchen vagina in the North Levantine Sea (Turkish coast), suggests the start of spreading of this Lessepsian immigrant in the Mediterranean Sea. The findings of the following species indicate the extension of their occurrence in the Mediterranean Sea: the foraminifer Amphistegina lobifera (island of Zakynthos, Greece), the medusa Cassiopea andromeda (Syria), the copepod Centropages furcatus (Aegean Sea), the decapod shrimp Melicertus hathor (island of Kastellorizo, Greece), the crab Menoethius monoceros (Gulf of Tunis), the barnacles Balanus trigonus, Megabalanus tintinnabulum, Megabalanus coccopoma and the bivalves Chama asperella, Cucurbitula cymbium (Saronikos Gulf, Greece).

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Unsupervised and supervised classification of hyperspectral imaging data using projection pursuit and Markov random field segmentation - A. Sarkar; A. Vulimiri; S. Paul; Jawaid Iqbal; A. Banerjee; R. Chatterjee; S. S. Ray (International Journal of Remote Sensing, 2012)

A study on the waste metal remediation using floriculture at East Calcutta Wetlands, a Ramsar site in India - Soumya Chatterjee; Lokendra Singh; Buddhadeb Chattopadhyay; Siddhartha Datta; S. K. Mukhopadhyay (Environmental Monitoring and Assessment, 2012)

A new atlas of temperature and salinity for the North Indian Ocean - A CHATTERJEE; D SHANKAR; S S C SHENOI; G V REDDY; G S MICHAEL; M RAVICHANDRAN; V V GOPALKRISHNA; E P RAMA RAO; T V S UDAYA BHASKAR; V N SANJEEVAN (Journal of Earth System Science, 2012)

Fine mode aerosol chemistry over a tropical urban atmosphere: characterization of ionic and carbonaceous species - A. Chatterjee; C. Dutta; T. K. Jana; S. Sen (Journal of Atmospheric Chemistry, 2012)

Acute and chronic effects of endosulfan on the haemato-immunological and histopathological responses of a threatened freshwater fish, spotted murrel, Channa punctatus - Kamal Sarma; A. K. Pal; N. P. Sahu; R. S. Dalvi; Nirupama Chatterjee; S. C. Mukherjee; Kartik Baruah (Fish Physiology and Biochemistry, 2012)

Fine mapping of 14q24.1 breast cancer susceptibility locus - Phoebe Lee; Yi-Ping Fu; Jonine D. Figueroa; Ludmila Prokunina-Olsson; Jesus Gonzalez-Bosquet; Peter Kraft; Zhaoming Wang; Kevin B. Jacobs; Meredith Yeager; Marie-Josèphe Horner; Susan E. Hankinson; Amy Hutchinson; et al. (Human Genetics, 2012)

Genetic analysis of juvenile growth and carcass traits in a full diallel mating in selected colored broiler lines - Ullengala Rajkumar; R. P. Sharma; M. K. Padhi; K. S. Rajaravindra; B. L. N. Reddy; M. Niranjan; T. K. Bhattacharya; S. Haunshi; R. N. Chatterjee (Tropical Animal Health and Production, 2011)

A study on the phytoaccumulation of waste elements in wetland plants of a Ramsar site in India - Soumya Chatterjee; Mridul Chetia; Lokendra Singh; Buddhadeb Chattopadhyay; Siddhartha Datta; S. K. Mukhopadhyay (Environmental Monitoring and Assessment, 2011)

Monitoring waste metal pollution at Ganga Estuary via the East Calcutta Wetland areas - Soumya Chatterjee; Buddhadeb Chattopadhyay; S. K. Mukhopadhyay (Environmental Monitoring and Assessment, 2010)

Effect of stocking density and journey length on the welfare of rohu (Labeo rohita Hamilton) fry - N. Chatterjee; A. K. Pal; T. Das; R. Dalvi; M. S. Mohammad; K. Sarma; S. C. Mukherjee; K. Baruah (Aquaculture International, 2010)

Quantification and Source Identification of Polycyclic Aromatic Hydrocarbons in Core Sediments from Sundarban Mangrove Wetland, India - C. Domínguez; S. K. Sarkar; A. Bhattacharya; M. Chatterjee; B. D. Bhattacharya; E. Jover; J. Albaigés; J. M. Bayona; Md. A. Alam; K. K. Satpathy (Archives of Environmental Contamination and Toxicology, 2010)

Simulated microgravity perturbs actin polymerization to promote nitric oxide-associated migration in human immortalized Eahy926 cells - Jamila H. Siamwala; S. Himabindu Reddy; Syamantak Majumder; Gopi Krishna Kolluru; Ajit Muley; Swaraj Sinha; Suvro Chatterjee (Protoplasma, 2010)

Suppression of the Inflammatory Cascade is Implicated in Resveratrol Chemoprevention of Experimental Hepatocarcinogenesis - Anupam Bishayee; Abhijeet Waghray; Kendra F. Barnes; Thomas Mbimba; Deepak Bhatia; Malay Chatterjee; Altaf S. Darvesh (Pharmaceutical Research, 2010)

Microalbuminuria: An inexpensive, non invasive bedside tool to predict outcome in critically ill patients - Surupa Basu; S. Chaudhuri; M. Bhattacharyya; T. K. Chatterjee; S. Todi; A. Majumdar (Indian Journal of Clinical Biochemistry, 2010)

Acid leachable trace metals in sediment cores from Sunderban Mangrove Wetland, India: an approach towards regular monitoring - M. P. Jonathan; S. K. Sarkar; P. D. Roy; Md. A. Alam; M. Chatterjee; B. D. Bhattacharya; A. Bhattacharya; K. K. Satpathy (Ecotoxicology, 2010)

Use of a novel anti-proliferative compound coated on a biopolymer to mitigate platelet-derived growth factor-induced proliferation in human aortic smooth muscle cells: comparison with sirolimus - Yong-Dan Tang; Ambarish Pandey; Antonina Kolmakova; Xin-Tong Wang; Subbu S. Venkatraman; Subroto Chatterjee; Freddy Y. C. Boey (Glycoconjugate Journal, 2009)

Polycyclic Aromatic Hydrocarbons in Intertidal Marine Bivalves of Sunderban Mangrove Wetland, India: An Approach to Bioindicator Species - O. Zuloaga; A. Prieto; A. Usobiaga; S. K. Sarkar; M. Chatterjee; B. D. Bhattacharya; A. Bhattacharya; Md. A. Alam; K. K. Satpathy (Water, Air, & Soil Pollution, 2009)

Post-harvest decline in commerical cane sugar and its relationship with quality parameters in sugarcane under sub-tropical climate - Parul Srivastava; C. Chatterjee; A. K. Shrivastava; S. Solomon; A. K. Srivastava; B. K. Dube (Sugar Tech, 2009)

Proctolaclaps regalis usages Drosophila eggs and pupae as ovipositional substrate and their lifecycle closely mimics the life cycle of Drosophila - P. Chatterjee; S. Banerjee; R. N. Chatterjee (Proceedings of the Zoological Society, 2009)

The role of copper in drug-resistant murine and human tumors - S. Majumder; S. Chatterjee; Smarajit Pal; J. Biswas; T. Efferth; Soumitra Kumar Choudhuri (BioMetals, 2009)

Flood inundation modeling using MIKE FLOOD and remote sensing data - S. Patro; C. Chatterjee; S. Mohanty; R. Singh; N. S. Raghuwanshi (Journal of the Indian Society of Remote Sensing, 2009)

Assaying Baseline Status of Particulate Laden Polyaromatic Hydrocarbon for a Grass Root Level Industrial Project - Girish Himatlal Pandya; N. Chatterjee; Ritesh Singh; Sanjay Kashyap; S. Pentu Saheb; S. R. Wate (Bulletin of Environmental Contamination and Toxicology, 2009)

Mixing ratios of carbonyls and BTEX in ambient air of Kolkata, India and their associated health risk - C. Dutta; D. Som; A. Chatterjee; A. K. Mukherjee; T. K. Jana; S. Sen (Environmental Monitoring and Assessment, 2009)

Expression of callose synthase genes and its connection with Npr1 signaling pathway during pathogen infection - Xiaoyun Dong; Zonglie Hong; Jayanta Chatterjee; Sunghan Kim; Desh Pal S. Verma (Planta, 2008)

Study of the potential of alternative crops by integration of multisource data using a neuro‐fuzzy technique - Anjan Sarkar; Arka Majumdar; Shaunak Chatterjee; Debapriya Chatterjee; Shibendu S. Ray; B. Kartikeyan (International Journal of Remote Sensing, 2008)

Organochlorine Pesticide Residues in Sediment Cores of Sunderban Wetland, Northeastern Part of Bay of Bengal, India, and Their Ecotoxicological Significance - S. K. Sarkar; A. Binelli; C. Riva; M. Parolini; M. Chatterjee; A. K. Bhattacharya; B. D. Bhattacharya; K. K. Satpathy (Archives of Environmental Contamination and Toxicology, 2008)

An Assessment of Mercury Loading in Core Sediments of Sunderban Mangrove Wetland, India (A Preliminary Report) - Ž. Kwokal; S. K. Sarkar; M. Chatterjee; S. Franciskovis-Bilinski; H. Bilinski; A. Bhattacharya; B. D. Bhattacharya; Md. Aftab Alam (Bulletin of Environmental Contamination and Toxicology, 2008)

Influence of progressive staling on germination of sugarcane - A. K. Shrivastava; S. Solomon; A. K. Srivastava; S. P. Shukla; A. Sawnani; R. Darash; C. Prajapati; Pushpa Singh; Priyanka Singh; R. K. Rai; R. Jain; Parul Srivastava; et al. (Sugar Tech, 2008)

Acquisition, transmission and host range of a begomovirus associated with yellow vein mosaic disease of mesta ( Hibiscus cannabinus and Hibiscus sabdariffa ) - A. Chatterjee; A. Roy; S. K. Ghosh (Australasian Plant Pathology, 2008)

Utilization of high resolution satellite gravity over the Carlsberg Ridge - S. Chatterjee; R. Bhattacharyya; T. J. Majumdar (Marine Geophysical Research, 2007)

A new monopartite begomovirus isolated from Hibiscus cannabinus L. in India - A. Chatterjee; S. K. Ghosh (Archives of Virology, 2007)

Genetic variation in catechol-O-methyltransferase (COMT) and obesity in the prostate, lung, colorectal, and ovarian (PLCO) cancer screening trial - Sophia S. Wang; Lindsay M. Morton; Andrew W. Bergen; Elizabeth Z. Lan; Nilanjan Chatterjee; Paul Kvale; Richard B. Hayes; Stephen J. Chanock; Neil E. Caporaso (Human Genetics, 2007)

Generation and study of high‐resolution satellite gravity over the Sumatran earthquake region - S. Chatterjee; R. Bhattacharyya; T. J. Majumdar (International Journal of Remote Sensing, 2007)

Structural and Functional Analysis of Rice Catalase-B Gene Promoter: Presence of Dof and CAAT Binding Site - P. Mondal; N. Dey; A. K. Dash; A. Chatterjee; B. B. Sahu; B. Panda; I. B. Maiti; S. C. Sabat (Plant Molecular Biology Reporter, 2007)

Estimating age-specific breast cancer risks: a descriptive tool to identify age interactions - William F. Anderson; Rayna K. Matsuno; Mark E. Sherman; Jolanta Lissowska; Mitchell H. Gail; Louise A. Brinton; Xiaohong (Rose) Yang; Beata Peplonska; Bingshu E. Chen; Philip S. Rosenberg; Nilanjan Chatterjee; Neonila Szeszenia-Dąbrowska; et al. (Cancer Causes & Control, 2007)

Transgenic Indian mustard (Brassica juncea) expressing tomato glucanase leads to arrested growth of Alternaria brassicae - Kalyan K. Mondal; R. C. Bhattacharya; K. R. Koundal; S. C. Chatterjee (Plant Cell Reports, 2007)

Genotypic variability in vegetable amaranth (Amaranthus tricolor L for foliage yield and its contributing traits over successive cuttings and years - S. Shukla; A. Bhargava; A. Chatterjee; A. Srivastava; S. P. Singh (Euphytica, 2006)

Phytotoxic Effect of Coal Mine Effluent on Growth Behavior, Betabolic Changes, and Metal Accumulation in Rice Plants (Oryza sativa L.) c.v. IR-36 - K. K. Tiwari; S. Dwivedi; U. N. Rai; A. K. Pandey; C. Chatterjee; N. K. Singh; R. D. Tripathi (Bulletin of Environmental Contamination and Toxicology, 2006)

Characterisation of disproportionating enzyme from wheat endosperm - Nicole S. Bresolin; Zhongyi Li; Behjat Kosar-Hashemi; Ian J. Tetlow; Manash Chatterjee; Sadequr Rahman; Matthew K. Morell; Crispin A. Howitt (Planta, 2006)

Alkaloid Spectrum of Different Germplasm Lines in Opium Poppy (Papaver somniferum L.) - Sudhir Shukla; S. P. Singh; H. K. Yadav; A. Chatterjee (Genetic Resources and Crop Evolution, 2006)

Caspase-3 Induced Apoptosis in Transgenic Zebrafish - Chiranjib Chakraborty; Gargi Saha; Biplab Sarkar; S. Pal; T. K. Chatterjee; A. K. Sadhu (Biotechnology Letters, 2006)

Integrating Remote Sensing and GIS Techniques with Groundwater Flow Modeling for Assessment of Waterlogged Areas - C. Chatterjee; Rakesh Kumar; B. Chakravorty; A. K. Lohani; S. Kumar (Water Resources Management, 2005)

Molecular Analysis of Divergence in Tachinid Uzi (Exorista Sorbillans) Populations in India - S. N. Chatterjee; T. Taraphdar; T. P. Mohandas (Genetica, 2005)

Classification of black decorative stones from Warangal District, Andhra Pradesh, India - Tarun Kumar Chatterjee; Rima Chatterjee; S. K. Singh (Bulletin of Engineering Geology and the Environment, 2005)

Molecular characterization of mulberry genetic resources indigenous to India - K. Vijayan; C. V. Nair; S. N. Chatterjee (Genetic Resources and Crop Evolution, 2005)

Evidence for oxidative stress in osteoarthritis - M Maneesh; H Jayalekshmi; T Suma; S Chatterjee; A Chakrabarti; T A Singh (Indian Journal of Clinical Biochemistry, 2005)

Occurrence of a Begomovirus with yellow vein mosaic disease of mesta ( Hibiscus cannabinus and Hibiscus sabdariffa ) - A. Chatterjee; A. Roy; K. V. Padmalatha; V. G. Malathi; S. K. Ghosh (Australasian Plant Pathology, 2005)

A Breadth Averaged Numerical Model for Suspended Sediment Transport in Hooghly Estuary, East Coast of India - P. C. Sinha; Pragya Guliani; G. K. Jena; A. D. Rao; S. K. Dube; A. K. Chatterjee; Tad Murty (Natural Hazards, 2004)

ISSR profiling of Indian cultivars of mulberry (Morus spp.) and its relevance to breeding programs - K. Vijayan; S. N. Chatterjee (Euphytica, 2003)

Persistence and Effectiveness of Iprodione Against Alternaria blight in Mustard - I. Mukherjee; M. Gopal; S. C. Chatterjee (Bulletin of Environmental Contamination and Toxicology, 2003)

Removal of carboxymethyl cellulase activity from the culture filtrate of Termitomyces clypeatus producing xylanase - A.K. Ghosh; M.L. Jana; A.K. Naskar; R. Chatterjee; S. Sengupta (Biotechnology Letters, 2002)

Modulating Action of Hyperforin on the P-Type Calcium Channels in the Membranes of Rat Cerebellar Purkinje Neurons - A. I. Fisyunov; N. A. Lozovaya; T. Sh. Tsyntsadze; N. M. Yatsenko; S. Chatterjee; O. A. Krishtal (Neurophysiology, 2001)

Responses of phosphate solubilizing bacteria to qualitatively different fertilization in simulated and natural fish ponds - B.B. Jana; J. Chatterjee; S. Ganguly; T. Jana (Aquaculture International, 2001)

Changes In The Stream Courses Around Maithon Reservoir, Eastern India: Observations Using Remote Sensing Data - S. Sengupta; A. Chatterjee (Journal of the Indian Society of Remote Sensing, 2000)

Biogeochemical cycling bacterial activity in response to lime and fertilizer applications in pond systems - S. Ganguly; J. Chatterjee; B.B. Jana (Aquaculture International, 2000)

Residues of Amitraz, a New Acaricide, on Tea - T. Saha; S. Chatterjee; K. Saha; A. Chowdhury; A. K. Somchoudhury; A. Bhattacharyya (Bulletin of Environmental Contamination and Toxicology, 2000)

Residues of Amitraz, a New Acaricide, on Tea - T. Saha; S. Chatterjee; K. Saha; A. Chowdhury; A. K. Somchoudhury; A. Bhattacharyya (Bulletin of Environmental Contamination and Toxicology, 2000)

Separation and identification of thyroid autoantibodies in patients with thyroid disorders by hydrophobic column - Pranab S. Basu; Ramdhan Majhi; Sudip Chatterjee; Sandip K Batabyal (Indian Journal of Clinical Biochemistry, 2000)

An Outbreak of Gangrenous Syndrome among Buffaloes and Cattle in West Bengal: Clinicopathological Studies - A. Sikdar; G.C. Chakraborty; D. Bhattacharya; S. Bakshi; D.K. Basak; A. Chatterjee; S.K. Halder (Tropical Animal Health and Production, 2000)

Effect of high altitude on sensitivity to the taste of phenylthiocarbamide - S. B. Singh; A. Chatterjee; U. Panjwani; D. K. Yadav; W. Selvamurthy; K. N. Sharma (International Journal of Biometeorology, 2000)

Gravity-directed calcium current in germinating spores of Ceratopteris richardii - Ani Chatterjee; D. Marshall Porterfield; Peter S. Smith; Stanley J. Roux (Planta, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Impact of Carbofuran in the Oocyte Maturation of Catfish, Heteropenustes fossilis (Bloch) - S. Chatterjee; A. B. Dutta; R. Ghosh (Archives of Environmental Contamination and Toxicology, 1997)

Zinc and iron as bioindicators of precancerous nature of oral submucuos fibrosis - R. R. Paul; J. Chatterjee; A. K. Das; S. K. Dutta; D. Roy (Biological Trace Element Research, 1996)

Low-level X-ray exposures on rat skin - Jyotirmoy Chatterjee; Kuntala De; S. K. Basu; A. K. Das (Biological Trace Element Research, 1994)

Trace metal levels of X-ray technicians' blood and hair - J. Chatterjee; B. B. Mukherjee; K. De; A. K. Das; S. K. Basu (Biological Trace Element Research, 1994)

Induction of SOS like responses by nitrofurantoin in Vibrio cholerae el tor cells - Md. S. Rahman; A. K. Pal; S. N. Chatterjee (Archives of Microbiology, 1993)

Suppressive effect of quinalphos on the activity of accessory sex glands and plasma concentrations of gonadotrophins and testosterone in rats - A. Ray; S. Chatterjee; S. Ghosh; S. N. Kabir; A. Pakrashi; C. Deb (Archives of Environmental Contamination and Toxicology, 1991)

Effects of L-ascorbic acid supplementation on dieldrin toxicity in rats - S. K. Bandyopadhyay; R. K. Tiwari; A. Mitra; B. Mukherjee; A. Banerjee; G. C. Chatterjee (Archives of Toxicology, 1982)

Antimicrobial activities of some antineoplastic and other withanolides - S. Chatterjee; S. K. Chakraborti (Antonie van Leeuwenhoek, 1980)